Step-by-step explanation:
x+y=5
3x-2y+5=0
3x-2y= -5
x+y=5...... equation 1
3x-2y= -5....... equation 2
there fore make x the subject of the formula in equation 1
x=5-y.. equation 3
substitute equation three in equation 2
3(5-y)-2y=-5
15y-3y-2y=-5
10y=-5
divide both sides by 10
y=-5/10
y=-½
substitute y into equation 1
x+(-½)=5
x=5+½
x=5½
x=5½,y= -½
Answer:
I believe it would be A bc
Step-by-step explanation:
A= 42
B= 32
C= 20
D= 36
Yes and no. It depends on the situation and how you're asking
Answer:
The result is 60
Step-by-step explanation:
We have to use this expression showing BODMAS rule. According to the rule, we must first solve the brackets. In our expression, the term within the bracket is (12-4) squared = (8) squared = 64.
Then we need to perform the addition followed by subtraction.
The expression becomes:
11 squared - 64 + 3
= 121 - 64 + 3
= 124 - 64
= 60
So, the result of the expression is 60.